Mapping the Profit Motive: A Comparative Analysis of For-Profit and Non-Profit Charter Schools - William Brett Robertson (Education Policy Analysis Archives, 2015)
For-profit charter schools represent a controversial new market-based education reform (Garcia, Barber, Molnar, 2009; Conn, 2002). This essay explores how schools operated by for-profit corporations differ from those operated by non-profit organizations. Specifically, do for-profit charter schools locate in demographically distinct areas and serve different student populations than similar schools operated by non-profit providers? Research suggests that charter school operators in some districts appear to strategically locate their schools in an effort to exclude certain student populations (Lubienski, Gulosino, Weitzel, 2009). If charter schools seek to exclude certain students, as these schools proliferate in a district or region there may be an intensifying stratification effect detrimental to the most disadvantaged students (Bifulco, Ladd, Ross, 2009). This essay undertakes a broad comparative analysis of the neighborhood demographic and student population characteristics of charter schools operated by for-profit corporations and nonprofit organizations, using multilevel modeling and geographic information systems, to compare the two school types across dissimilar state contexts. In so doing, the study seeks to isolate the impact of a school being operated by a for-profit corporation and illuminate what impact the proliferation of for-profit schools might have on the distribution of student populations across regions.